PENGARUH PENGGUNAAN GAME EDUKASI BERBASIS WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI MENULIS TEKS PROSEDUR SISWA KELAS V SD NEGERI UJUNG TANAH 2 KOTA MAKASSAR - Nur Afmi Irbar; Aliem Bahri; Anin Asnidar (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2025)
This research explored the impact of utilizing Wordwall-based educational games on the procedural writing learning outcomes of fifth-grade students at SD Negeri Ujung Tanah 2 Makassar. Addressing the issue of students' underdeveloped writing skills, potentially linked to a scarcity of engaging instructional resources, the study adopted a quantitative methodology with a one-group pretest-posttest design involving 30 students. The analysis of learning outcome data, conducted using a t-test with SPSS, showed a substantial increase in the average score from 28.17 to 85.83 (p < 0.05). These results indicate that the integration of Wordwall educational games had a positive and significant effect on the students' procedural text writing abilities.